The Fujoshi Phenomenon Among Teenagers with Manhwa Boys Love Channel on Telegram - Risma Wardani (Green Publisher Indonesia, 2024)
The purpose of this study is to explain the factors that affect the interest and motivation of fujoshi in creating a manhwa boys love channel on Telegram. This is interesting to research because it is a sexual deviation that is still taboo among society today. This research uses the phenomenological theory of Alfred Schutz which explains about human actions that are influenced by causal motives and goal motives. This study uses a qualitative method approach. The informant selection technique used is purposive sampling. There are 5 fujoshi informants who are 17-22 years old and have a manhwa boys love channel on the Telegram application. Data collection was carried out through observation of the content of the boys love manhwa channel on Telegram. An in-depth interview discussing the reasons and goals of fujoshi for creating a manhwa boys love channel on Telegram. In addition, documentation is also carried out by saving screenshots of content published by fujoshi on Telegram. Data analysis was carried out using the Miles and Huberman model including data collection, data reduction, data presentation and conclusion drawn. The results of the study show several reasons why fujoshi created a manhwa boys love channel on Telegram. First, because they got an offer from a friend, wanted to try new things, the hiatus phase and liked the romance of boys love. The purpose of creating a manhwa boys love channel on Telegram by fujoshi is to channel hobbies and connect people with similar interests.